Association of Bilateral Acute Anterior Uveitis with a Capsaicin Patch. (3rd June 2013) - Bleuel, Irina; Zinkernagel, Martin; Tschopp, Markus; Tappeiner, Christoph
Abstract: Purpose : To report a case of bilateral acute anterior uveitis in association with the application of an analgesic transdermal capsaicin patch. Methods : Case report and review of literature. Results : A 38-year-old woman suffered from bilateral acute anterior uveitis, manifesting 12–24 h after application of an analgesic capsaicin patch (Isola Capsicum N Plus) that served to alleviate muscular neck pain. Systemic immune-mediated and infectious diseases were excluded by medical history and laboratory testing. Control of inflammation was achieved with topical corticosteroid treatment within 1 week. Over the course of a 1-year follow-up, no further recurrence of uveitis was observed. Conclusions : The case suggests a possible association of capsaicin-containing transdermal patches and acute anterior uveitis.